A Magnaporthe Chitinase Interacts with a Rice Jacalin-Related Lectin to Promote Host Colonization. Issue 4 (29th January 2019) - Han, Yijuan; Song, Linlin; Peng, Changlin; Liu, Xin; Liu, Lihua; Zhang, Yunhui; Wang, Wenzong; Zhou, Jie; Wang, Shihua; Ebbole, Daniel; Wang, Zonghua; Lu, Guo-dong
Abstract : A chitinase from the rice blast fungus (Magnaporthe oryzae) targets a rice (Oryza sativa) lectin to suppress plant immune response. Abstract: The genome of rice blast fungus ( Magnaporthe oryzae ) encodes 15 glycoside hydrolase 18 family chitinases. In this study, we characterized the function of an M. oryzae extracellular chitinase, MoChi1, and its interaction with a host protein, OsMBL1, a jacalin-related Mannose-Binding Lectin (MBL) in rice ( Oryza sativa ). Deletion of MoChi1 resulted in reduced aerial hyphal formation and reduced virulence in rice by activating the expression of defense-responsive genes. We confirmed MoChi1 interaction with rice OsMBL1 in vitro and in vivo. OsMBL1 was induced by pathogen-associated molecular patterns and M. oryzae infection. Overexpression of OsMBL1 led to activation of rice defense-responsive genes and a chitin-induced reactive oxygen species burst, thereby enhancing resistance to M. oryzae . Knockdown of OsMBL1 enhances susceptibility of rice plants to M. oryzae . Furthermore, MoChi1 suppressed chitin-induced reactive oxygen species in rice cells and competed with OsMBL1 for chitin binding. Taken together, our study reveals a mechanism in which MoChi1 targets a host lectin to suppress rice immunity.